A Comprehensive Comparison Between Virtual and Traditional Laboratories in Engineering Education (Comprehensive Journal of Science, 2025)
Laboratory experiences are a cornerstone of engineering education, providing students with the opportunity to apply theoretical knowledge to practical problems. With the rise of digital technologies, virtual laboratories have emerged as a viable alternative to traditional hands-on laboratories. This article provides an in-depth comparison of virtual and traditional laboratories, examining their effectiveness, accessibility, cost, and impact on student learning outcomes. The discussion also explores the potential of a blended approach, combining the strengths of both methods to create a more comprehensive educational experience. The findings suggest that while traditional laboratories offer invaluable hands-on experience, virtual laboratories provide flexibility, scalability, and opportunities for remote learning. The article concludes with recommendations for integrating both approaches into engineering curricula.
Keywords: virtual laboratories, traditional laboratories, engineering curricula